2022
DOI: 10.1292/jvms.22-0207
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of a recombinant hemagglutinin neuraminidase-<i>Porcine rubulavirus</i> produced by <i>Escherichia coli</i> of <i>Porcine rubulavirus</i> gives protective immunity of litter after challenge

Abstract: Porcine rubulavirus (PRV) is a contagious virus that affects the Mexican swine industry. This work aimed to evaluate the immunogenicity of an rHN-PorPV candidate vaccine on pregnant sows, and the protective efficacy afforded to their 7-day-old suckling piglets against PRV lethal challenge. Three sows were immunized with rHN-PorPV formulated with immunestimulating complex (ISCOMs) and two sows with rHN-PorPV protein alone as well as a mock-immunized pregnant sow (negative control). Quantitative ELISA detected a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
(80 reference statements)
0
1
0
Order By: Relevance
“…The antibody response was dramatically higher using a Matrix-M TM as an adjuvant. Matrix-M TM selection was according to our research group [ 55 , 72 , 73 ]; we have observed that this immunostimulatory complex is an adjuvant that enhances strong immunogenicity using advanced technology in a nanocarrier to deliver antigens [ 59 ]. These results are in agreement with previously reported studies, which described antigen enhanced with Matrix-M TM as being highly immunogenic and inducing both antibody and cellular immune responses [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…The antibody response was dramatically higher using a Matrix-M TM as an adjuvant. Matrix-M TM selection was according to our research group [ 55 , 72 , 73 ]; we have observed that this immunostimulatory complex is an adjuvant that enhances strong immunogenicity using advanced technology in a nanocarrier to deliver antigens [ 59 ]. These results are in agreement with previously reported studies, which described antigen enhanced with Matrix-M TM as being highly immunogenic and inducing both antibody and cellular immune responses [ 57 ].…”
Section: Discussionmentioning
confidence: 99%